Internal efficiency of nutrient utilization: what is it and how to measure it during vegetative plant growth? - Santa Maria, Guillermo Esteban (2015)
Efficient use of the resources required by plants to sustain crop production is considered an important objective in agriculture. In this context, the idea of developing crops with an enhanced ability to utilize mineral nutrients already taken up by roots has been proposed. In recent years powerful tools that allow the association of phenotypic variation with high-resolution genetic maps of crop plants have also emerged. To take advantage of these tools, accurate methods are needed to estimate the internal efficiency of nutrient utilization (ENU) at the whole-plant level, which requires using suitable conceptual and experimental approaches. Here we highlight some inconsistencies in the definitions of ENU commonly used for ENU ‘phenotyping’ at the vegetative stage and suggest that it would be convenient to adopt a dynamic definition. The idea that ENU should provide information about the relationship between carbon and mineral nutrient economies mainly during the period under which growth is actually affected by low internal nutrient concentration is here advocated as a guide for the selection of adequate operational ENU formulae for the vegetative stage. The desirability of using experimental approaches that allow removal of the influence of nutrient acquisition efficiency on ENU estimations is highlighted. It is proposed that the use of simulation models could help refine the conclusions obtained through these experimental procedures. Some potential limitations in breeding for high ENU are also considered.